Efficacy of Once Daily versus Divided Daily Administration of Low Daily Dosage (15 mg/Day) of Methimazole in the Induction of Euthyroidism in Graves’ Hyperthyroidism: A Randomized Controlled Study - Sutin Sriussadaporn; Wanwaroon Pumchumpol; Raweewan Lertwattanarak; Tada Kunavisarut (International Journal of Endocrinology)
Background. Previous studies used unequal or high daily dosages of methimazole (MMI) to compare the efficacy of once daily dose regimen (OD-MMI) with that of divided daily doses regimen (DD-MMI) in inducing euthyroidism. Objectives. To compare the efficacy of OD-MMI to that of DD-MMI using low daily dosage of MMI in inducing euthyroidism. Methods. Fifty patients with clinically nonsevere Graves’ hyperthyroidism were randomized to be treated with 15 mg/day OD-MMI or 15 mg/day DD-MMI. Results. 21 cases (84%) in OD-MMI and 23 cases (92%) in DD-MMI were eligible for analyses. During the treatment, there was no difference in baseline characteristics, serum FT3 and FT4 reductions, and cumulative rate of achieving euthyroidism (4.8% versus 4.3%, 28.6% versus 34.8%, 71.4% versus 82.6%, and 85.7% versus 87.0% at 2, 4, 8, and 12 weeks, resp.) between both regimens. Hypothyroidism developed in DD-MMI significantly more than in OD-MMI (17.4% versus 0%, p<0.05). Conclusions. Treatment with MMI at a low daily dosage of 15 mg/day OD-MMI is as effective as DD-MMI in the reduction of serum thyroid hormone levels and induction of euthyroidism. The OD-MMI regimen is preferable to the DD-MMI regimen in the treatment of clinically nonsevere Graves’ hyperthyroidism. This trial is registered with Thai Clinical Trials Registry: TCTR20170529001.